2019
DOI: 10.1107/s205225251801686x
|View full text |Cite
|
Sign up to set email alerts
|

A jumping crystal predicted with molecular dynamics and analysed with TLS refinement against powder diffraction data

Abstract: A phase transition in a jumping crystal is predicted using molecular dynamics. The resulting structure and the dynamics of the transition are verfied by TLS refinement against powder diffraction data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Solving the molecular structure of such products requires, therefore, X-ray powder diffraction (XRD). Here, MD can assist by simulating the dehydration process; the XRD pattern of the dehydrated state found in the simulation can then be compared with an experimental powder pattern to solve the structure of the new phase [442,443]. Using MD-based free-energy perturbation methods, the free energy of inclusion of a solvated molecule can be calculated, which is relevant for understanding the stability of a hydrate [444].…”
Section: Studies Of Crystalline and Amorphous Solidsmentioning
confidence: 99%
“…Solving the molecular structure of such products requires, therefore, X-ray powder diffraction (XRD). Here, MD can assist by simulating the dehydration process; the XRD pattern of the dehydrated state found in the simulation can then be compared with an experimental powder pattern to solve the structure of the new phase [442,443]. Using MD-based free-energy perturbation methods, the free energy of inclusion of a solvated molecule can be calculated, which is relevant for understanding the stability of a hydrate [444].…”
Section: Studies Of Crystalline and Amorphous Solidsmentioning
confidence: 99%
“…Classical molecular dynamics (C-MD) is much more affordable and can deal with computational boxes of hundreds or thousands of molecules, and, at variance with simple minimization procedures, it can explicitly account for finite T and p effects. C-MD requires careful calibration of intermolecular potentials; besides, being an equipartition-regime technique, it suffers from the absence of quantum effects. , Its results are however quite trustworthy at or around room temperatures as demonstrated by a vast literature. , Its performance in high pressure or anisotropic environments need be carefully validated, and this will be one of the aims of the present paper.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that the librations are strongly influenced by the phase transition and are not well-defined in the β-polymorph. A recently study on thermosalient crystals of perhydropyrene, which is a polycyclic hydrocarbon similarly to coronene, showed that the librations play key roles in the thermosalient phase transition 33 . Therefore, it is suggested that the librations are also critically involved in the phase transition of the coronene nanofibers.…”
Section: Resultsmentioning
confidence: 99%